Social Conditioning of Criminal Law Rules Governing the Responsibility of Medical Workers in the Republic of Kazakhstan - YESPERGENOV, Yevgeniya Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The present article studies one of the most important properties of criminal law provisions regulating the responsibility of medical workers in the Republic of Kazakhstan, namely their social conditioning. Criminal responsibility of medical workers, although indirectly, has a significant impact on the quality of medical services and the state of health in general; therefore, the investigation of the relevant criminal provisions in terms of their social conditioning has a definite practical value. The aim of the present article is to analyze the influence of social conditioning on the formation of criminal law protecting the health of citizens. The article examines the international law governing the right of citizens to quality medical care, the penal legislation of Kazakhstan and the legislation of several countries regulating the criminal responsibility of medical professionals for the improper performance of their duties and unlawful acts against patients, the works of researchers who studied the social conditioning of the criminal law, the results of sociological surveys, statistics, conclusions and recommendations for further improvement of the criminal law protection of the health of citizens. On the basis of the conducted research, the author emphasized the close relationship of the social categories of criminal law, and how the social factors that shape the tasks of social life are embodied in the criminal law, formulated the proposals for further improvement of the criminal legislation of the Republic of Kazakhstan. A number of provisions, conclusions and proposals of the submitted articles can be used in scientific and teaching activities in addressing issues of crime investigation in the medical field, as well as the subsequent reform of the criminal law.